Thermokinetics of Catalytic Pyrolysis of Biomass for Production of Sustainable Energy - Razi Ahmad; Ye Lwin; Saiful Azhar Saad; K. Ismail (Universiti Malaysia Perlis (UniMAP), 2008)
Organized by Universiti Malaysia Perlis (UniMAP), 9th - 12th June 2007 at Park Royal Hotel, Penang.